(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This article describes the existing problem of the fruit sector that has affected MSEs in Teapa (Tabasco, Mexico) and has prevented business development. Therefore, this study focused on identifying fruit production and its use. The methodology was based on an exploratory and descriptive study. 105 agricultural producers from 7 rural localities participated, of which 85% were male and 15% were female, with a 95% confidence level and an 8.51% sampling error. A questionnaire consisting of 4 sections with 100 items was applied. In conclusion, fruit culture from the aforementioned town showed a smaller scale productive behavior due to important factors such as the access to government economic programs, aimed at the agricultural sector. According to results, 90% mentioned they haven’t been able to access financial support and only 10% have been supported. Similarly, agronomic management of fruit trees before and after production showed that 17.89% fertilized, 18.95% pruned, 23.16% used traditional techniques, 35.79% controlled pests and diseases, and 4.21% none.